2009
DOI: 10.1007/s00417-009-1082-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Müller glial cells in epiretinal membrane formation

Abstract: Alterations in the membrane conductance of Müller cells suggest that Müller cells may alter their phenotype into progenitor-like cells in the course of proliferative retinopathies; transdifferentiated Müller cells may have great impact for the development of new cell-based therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(134 citation statements)
references
References 216 publications
7
118
1
8
Order By: Relevance
“…21 In this study, specimens from MP demonstrated both distribution patterns, whereas specimens from VMTS presented cell cluster formation more frequently than homogenous cell distribution. On the one hand, one might speculate that this finding supports the hypothesis that epiretinal cell proliferation may be initiated by localized vitreoretinal traction 22 forming cell clusters that progress after a period to homogenous cell multilayers at the vitreal side of the ILM. Conversely, epiretinal cell proliferation may be initiated by vitreoretinal separation.…”
Section: Discussionsupporting
confidence: 62%
“…21 In this study, specimens from MP demonstrated both distribution patterns, whereas specimens from VMTS presented cell cluster formation more frequently than homogenous cell distribution. On the one hand, one might speculate that this finding supports the hypothesis that epiretinal cell proliferation may be initiated by localized vitreoretinal traction 22 forming cell clusters that progress after a period to homogenous cell multilayers at the vitreal side of the ILM. Conversely, epiretinal cell proliferation may be initiated by vitreoretinal separation.…”
Section: Discussionsupporting
confidence: 62%
“…retinal detachment and finally blindness (Bringmann and Wiedemann, 2009). Müller cells from patients with PVR exhibited upregulated currents through P2X7 receptors compared with normal donors, which led to increased activity of calcium-activated large-conductance potassium channels (Bringmann et al, 2001).…”
Section: Function and Therapeutic Potential Of Nucleotides In Eyementioning
confidence: 99%
“…15 In this study, we followed and recorded the evolution of preretinal blood under oil after diabetic vitrectomy to examine its reabsorption pattern and complications. Unlike the conventional concept which holds that preretinal blood almost always induces a thick fibrotic membrane and greatly disturbs vision, 16,17 our study showed that most Abbreviations: OP, operative; LogMAR, logarithm of minimum angle of resolution; F/U, follow-up; F, female; M, male. *Indicates recurrent epiretinal membrane.…”
Section: Discussionmentioning
confidence: 54%